Secondary adrenal insufficiency and pituitary dysfunction in oral/transdermal opioid users with non-cancer pain. Issue 6 (December 2018) - Lamprecht, Andrea; Sorbello, Jane; Jang, Christina; Torpy, David J; Inder, Warrick J
Abstract : Objective: To evaluate pituitary function, sexual function and quality of life (QoL) in patients on oral or transdermal opioids. Design and methods: Cross-sectional study comparing pituitary function, QoL and sexual function in people on long-term opioid therapy ( n = 40) vs an age- and sex-matched control group ( n = 25). Baseline pituitary function was assessed on blood samples collected prior to 0900 h. Further testing with corticotropin (250 µg IV) and metyrapone (30 mg/kg) stimulation tests was undertaken on participants with serum cortisol <250 nmol/L. Validated questionnaires completed to assess QoL, fatigue and sexual function. Results: Secondary adrenal insufficiency (SAI) was identified on the basis of a failed stimulation test in 22.5% of opioid users vs no controls ( P = 0.01). Opioid users with SAI had a higher median morphine-equivalent daily dose (MEDD), P = 0.037 – 50% with MEDD >200 mg and 0% with MEDD <60 mg had SAI. Among male participants, testosterone was inversely associated with BMI ( P = 0.001) but not opioid use. A non-significant trend to low testosterone <8 nmol/L in male opioid users (11/24 opioid users vs 2/14 control, P = 0.08) suggests a small subgroup with opioid-induced androgen deficiency. Opioid users had greater fatigue, reduced quality of life in all subsections of the SF-36 and impaired sexual function in both males and females (all scores P < 0.001 compared to controls). Conclusion: Long-term opioid therapy was associated with dose-related SAI in over 20% of chronic pain patients and is associated with poor quality of life, fatigue and sexual dysfunction. Obesity confounds the interpretation of opioid-induced male androgen deficiency.